Analytical Review of Shahid Naqvi's Naat and Manaqib - Nazir, Muhammad; Hasssan, Muhammad; Ali, Zulfiqar (sourcecoder, 2024)
Naat, an Arabic term, signifies praise, description, and commendation. In literary terminology, Naat refers to poetic compositions extolling the virtues and praises of the Prophet Muhammad (peace be upon him). The origins of Naat in Urdu poetry trace back to the Deccan region. Early Urdu mystic poems, such as masnavis, often included Naats.Sultan Muhammad Quli Qutb Shah, Urdu's first poet laureate, initiated systematic Naat recitation. His diwan contains over a dozen Naats. Prominent poets like Wali Dakhni, Amir Minai, Mohsin Kakorvi, Jigar Moradabadi, and Maher ul-Qadri followed suit. Among them, Shahid Naqvi, a renowned poet from Karachi, excelled in various forms of Urdu poetry. Shahid Naqvi's works encompass ghazal, nazm, marsiya, salam, qat'ah, ruba'i, Naat, and Manaqib. His notable collections include Nafs-e-Mutmain, Zameer-e-Maslub, Karb-e-Jawadan, Sirat-o-Sabil, Hisar-e-Haram, Kehkashan, and Rumal-e-Zahra. Naqvi's poetry exhibits mastery of poetic skills, continuous improvement, critical consciousness, and logical approach.Naat, Hamd, and Manaqib demand exceptional artistry and skill, which Naqvi possesses. His poetry centers around eternal truths, universal verities, and sincere expressions. Naqvi navigates complex poetic territories with ease, employing subtlety and intellectual depth. His Naats reflect modern style, beautiful expression, profound thought, and boundless devotion.Naqvi's Naats and Manaqib radiate spiritual fervor, exploring themes like Miraj (Prophet's ascension) and its metaphysical interpretations. His poetry transcends mere praise, delving into the depths of human experience and spiritual quest. Through his works, Naqvi solidifies his position as a leading Urdu poet, leaving an indelible mark on the literary landscape